The Influence of Parents on The Leadership of Children in The Family - As A Psychological Factor in Parenting - Murotmusaev Komiljon Buribaevich; Abduakhadova Mehribonu; Boykulova Mokhinur (Genius Journals, 2022)
The article examines the influence of parents on the formation of a child as a leader. The main qualities that a leader should have are listed. In accordance with these qualities recommendations for parents on The article discusses the influence of parents on the development of leadership qualities in their child
Keywords: Leadership; leader; honesty; intelligence